Unlocking the training process: how different training tasks shape the physiology and biomechanics of professional futsal players - Serrano, C.; Ferraz, A.; Ribeiro, J. N.; Ibañez, E.; Travassos, B. (Frontiers in Sports and Active Living, 2025)
Introduction: Despite the characterization of the physical and technical tactical demands of futsal SSCGs, there remains a need to better understand the physiological and biomechanical loads of each training task to determine its workload during training sessions further. The present study aims to analyze and classify the physiological and biomechanical demands of different futsal training tasks to enhance the understanding of these demands and their implications for elite futsal players` performance.